2020
DOI: 10.1038/s41467-019-13963-z
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont population control by host-symbiont metabolic interaction in Symbiodiniaceae-cnidarian associations

Abstract: In cnidarian-Symbiodiniaceae symbioses, algal endosymbiont population control within the host is needed to sustain a symbiotic relationship. However, the molecular mechanisms that underlie such population control are unclear. Here we show that a cnidarian host uses nitrogen limitation as a primary mechanism to control endosymbiont populations. Nitrogen acquisition and assimilation transcripts become elevated in symbiotic Breviolum minutum algae as they reach high-densities within the sea anemone host Exaiptasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
187
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(199 citation statements)
references
References 61 publications
10
187
2
Order By: Relevance
“…Host starvation typically results in nitrogen stress to the symbiont, which reduces metabolism and cell division (41,80). These decreased symbiont G 2 /M populations in hospite lend further support to the idea that nutrient limitation by the host is a strategy for symbiont regulation in nutrient-starved cnidarian hosts (79,81,91,92). Symbiont population growth is thought to rely on the assimilation of nitrogen in the form of waste ammonium from the host environment in order for successful colonization.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Host starvation typically results in nitrogen stress to the symbiont, which reduces metabolism and cell division (41,80). These decreased symbiont G 2 /M populations in hospite lend further support to the idea that nutrient limitation by the host is a strategy for symbiont regulation in nutrient-starved cnidarian hosts (79,81,91,92). Symbiont population growth is thought to rely on the assimilation of nitrogen in the form of waste ammonium from the host environment in order for successful colonization.…”
Section: Discussionmentioning
confidence: 77%
“…The overall increase in gastrodermal proliferation in symbiotic Aiptasia further supports a targeted expansion of the gastrodermis caused by the presence of symbiont populations. Further experiments could examine the host and symbiont cell proliferation under stable conditions, when host regulation of the symbiont cell cycle would be expected to slow symbiont proliferation as a result of nitrogen limitation (78)(79)(80)(81). In contrast to the fast-growing symbiont population densities of partially colonized hosts, these symbiont population densities within fully colonized cnidarian hosts have both elevated C/N ratios and elevated transcripts of genes involved in nitrogen assimilation, which would suggest a population control mechanism after colonization (81).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of either a coupled or uncoupled photosynthetic activity to respiration in Symbiodiniaceae, may also have implications for our understanding of their life in symbiosis. It is known that when in hospite , the Symbiodiniaceae cell division is strictly controlled and reduced by the animal hosts (Falkowski et al ., 1993; Xiang et al ., 2020). As cell division is directly linked to respiratory metabolism (which converts carbohydrates produced during photosynthesis into cellular metabolites used in the construction of cells; Falkowski et al ., 1985; Geider & Osborne, 1989), respiration rates must also be kept low when in hospite (Rädecker et al ., 2018; M. Pierangelini, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that coral get can control Symbiodiniaceae in three ways: 1) coral stimulates Symbiodiniaceae to release their photosynthates [48,49]; 2) coral digests/degrades Symbiodiniaceae to control Symbiodiniaceae density [50]; and 3) coral limits the nutrients uptake of Symbiodiniaceae [26,51]. In the present study, Symbiodiniaceae density did not increase signi cantly in 5 group, indicating that coral larvae might have regulated the Symbiodiniaceae density by digesting algae or limiting the nitrogen availability to avoid overgrowth of Symbiodiniaceae and to enhance the photosynthetic rate for high energy requirement.…”
Section: Coral-algal Symbiosis Work For Coral Meta-organism Adaptatimentioning
confidence: 99%